1987
DOI: 10.1007/bf00051853
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between single plant plots and five plant plots for the initial selection stage of a potato breeding programme

Abstract: The efficiency of single plant selection in the initial selection stage of a potato breeding programme was examined. A random sample of potato clones was grown in single plant plots and also in two replicates of five plant plots. After harvest, each plot was visually assessed by three potato breeders; total tuber weight and number of tubers per plant were also recorded, from which mean tuber weight was calculated. The error variances of the single plant plots were found to be significantly greater than from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Statistical analysis revealed clear environmental effects on yield, sugars, and French fry color characteristics from year to year. Several studies reported the environmental effects including Brown (1987), Maris (1988), Neele et al (1988). However, increasing the number of replicates per clone during early years of selection has a down-side that we experienced.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Statistical analysis revealed clear environmental effects on yield, sugars, and French fry color characteristics from year to year. Several studies reported the environmental effects including Brown (1987), Maris (1988), Neele et al (1988). However, increasing the number of replicates per clone during early years of selection has a down-side that we experienced.…”
Section: Discussionmentioning
confidence: 80%
“…Intraclonal selection was a useful means of generating better lines that will store longer with better French fry processing quality. Multigenic traits such as yield ) with high variability (Neele et al 1988;Jones and Cassells 1995) are difficult to improve as are processing traits (Douches and Freyre 1994), although processing traits have been considerably improved over the last 2 decades (Love et al 1998 Brown 1987), decreases environmental effects, and slightly enhances selection efficiency (Neele et al 1988). Statistical analysis revealed clear environmental effects on yield, sugars, and French fry color characteristics from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conducted with potato crops, such as those of Brown (1987) and Bearzoti & Pinto (1996), discussed the plot size based on the stage of the improvement program carried out with that crop, since initial phases, when there are too many genotypes to be tested and few tubers available, smaller plots should be prioritized, whereas in the following stages, with fewer genotypes to be tested and the need for detecting little meaningful differences between averages of clones, one should use larger plots, which could be associated with the method to be used, and also with the BU size.…”
Section: Resultsmentioning
confidence: 99%
“…Roraima s/n o , Bairro Camobi, 97105-900 Santa Maria-RS; E-mail: dilsonb@smail.ufsm.br; lindolfo@smail.ufsm.br Oliveira, 2005). Yield variation among plots depend upon genetic diversity (Brown, 1987), environmental conditions, inter and intra-plot competition and sampling technique (Smith, 1938;Gomez & Gomez, 1984;Steel et al, 1997).…”
Section: Plot Size Variation To Quantify Yield Of Potato Clonesmentioning
confidence: 99%
“…Since exact knowledge about the environmental variability of the experimental area is necessary to arrange more precise experiments, only unbiased estimations should be used to improve gain from selection in a particular step of the potato breeding program (Vermeer, 1990). Single-hill plots are not precise enough to detect differences among clones already selected in previous generations (Brown, 1987). Moreover, plots bigger than single hills are necessary to detect differences among clones in advanced selection steps (Bearzoti & Pinto, 1996).…”
Section: Plot Size Variation To Quantify Yield Of Potato Clonesmentioning
confidence: 99%